The role of accounting disclosure in granting bank financing A field study ona sample of banks operating in the state of Gezira 2022 AD: (دراسة ميدانية على عينة من المصارف العاملة في ولاية الجزيرة 2022م) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of the research is to identify the adequacy of accounting disclosure in granting bank financing in explaining the role of accounting disclosure in granting bank financing by linking the concepts of full, comprehensive and adequate disclosure to bank financing. The impact of full accounting disclosure on granting bank financing, the existence of an impact of comprehensive accounting disclosure on granting bank financing, the existence of an impact of adequate accounting disclosure on granting bank financing, and the research relied on the descriptive approach, the deductive and inductive approach, the inferential analytical approach, and the historical approach, and the research concluded several conclusions, including: The results revealed And the existence of an impact of accounting disclosure on bank financing through knowledge of the financial statements and the appropriate financial position for granting bank financing. The results of the study also showed that there is a strong impact of full, comprehensive and sufficient accounting disclosure on granting bank financing.